Expression of HOXA11 in the mid-luteal endometrium from women with endometriosis-associated infertility - Szczepańska Malgorzata; Wirstlein Przemyslaw; Skrzypczak Jana; Jagodziński Paweł P (BMC, 2012)
Abstract Background A decrease in HOXA11 expression in eutopic mid-secretory endometrium has been found in women with endometriosis-associated infertility. Methods Using Real-time quantitative PCR (RQ-PCR) and western blotting analysis we studied the HOXA11 transcript and protein levels in mid-luteal eutopic endometrium from eighteen infertile women with minimal endometriosis, sixteen healthy fertile women and sixteen infertile women with fallopian tubal occlusion from the Polish population. We also evaluated transcript levels of DNA methyltransferases DNMT1, DNMT3A and DNMT3B in these groups of women. Results There were significantly lower levels of HOXA11 transcripts (p = 0.003, p = 0.041) and protein (p = 0.004, p = 0.001) in women with endometriosis as compared to fertile women and infertile women with tubal occlusion. Moreover, we found significantly higher methylation levels of the CpG region in the first exon of HOXA11 in infertile women with endometriosis compared with fertile women (p < 0.001) and infertile women with tubal occlusion (p < 0.001). We also observed significantly increased levels of DNMT3A transcript in women with endometriosis than fertile women (p = 0.044) and infertile women with tubal occlusion (p = 0.047). However, we did not observe significant differences in DNMT1 and DNMT3B transcript levels between these investigated groups of women. Conclusions We confirmed that reduced HOXA11 expression may contribute to endometriosis-associated infertility. Moreover, we found that DNA hypermethylation can be one of the possible molecular mechanisms causing a decrease in HOXA11 expression in the eutopic mid-secretory endometrium in infertile women with endometriosis.